# A.2.7.2 Explaining Acceptable Moves

- Author:
- Katie Akesson

For the first 5 problems, explain what algebraic * moves* make the first equation

*to the second equation, so that if x is a solution to the first equation it will also be a solution to the second equation. 16 = 4(9 - x) 16 = 36 - 4x*

__equivelant__5x = 24 + 2x 3x = 24

-3(2x + 9) = 12 2x + 9 = -4

5x = 3 - x 5x = -x + 3

18 = 3x - 6 + x 18 = 4x - 6

For the next 5 problems, explain what algebraic * mistake* was made so that the first equation is

*NOT*to the second equation, so that if x is a solution to the first equation it will NOT be a solution to the second equation. Then

__equivelant__**- tell what the second equation should be to be so that it would be equivelant (but still a**

*fix the mistake**different*equation) to the first equation. 9x = 5x + 4 14x = 4

1/2x - 8 = 9 x - 8 = 18

6x - 6 = 3x x - 1 = 3x

-11(x - 2) = 8 x - 2 = 8 + 11

4 - 5x = 24 5x = 20